Drinking Water Disinfection Byproducts (DBPs) and Human Health Effects: Multidisciplinary Challenges and Opportunities - Li, Xing-Fang; Mitch, William A (Environmental science & technology, 2018)
While drinking water disinfection has effectively prevented waterborne diseases, an unintended consequence is the generation of disinfection byproducts (DBPs). Epidemiological studies have consistently observed an association between consumption of chlorinated drinking water with an increased risk of bladder cancer. Out of the >600 DBPs identified, regulations focus on a few classes, such as trihalomethanes (THMs), whose concentrations were hypothesized to correlate with the DBPs driving the toxicity of disinfected waters. However, the DBPs responsible for the bladder cancer association remain unclear. Utilities are switching away from a reliance on chlorination of pristine drinking water supplies to the application of new disinfectant combinations to waters impaired by wastewater effluents and algal blooms. In light of these changes in disinfection practice, this article discusses new approaches being taken by analytical chemists, engineers, toxicologists and epidemiologists to characterize the DBP classes driving disinfected water toxicity, and suggests that DBP exposure should be measured using other DBP classes in addition to THMs.